Logic, language, information, and computation : 25th International Workshop, WoLLIC 2018, Bogota, Colombia, July 24-27, 2018, Proceedings /: 25th International Workshop, WoLLIC 2018, Bogota, Colombia, July 24-27, 2018, Proceedings. (2018) - Unknown
No abstract available